L’IMPERFECTION DU MARCHE ET LA PERFORMANCE COMMERCIALE DE MARCHE DES VIVRES FRAIS ENTRE L’ECOP ET COMENAV A KISANGANI. - Salumu, Fiston WANDJA (IJRDO - Journal of Social Science and Humanities Research, 2023)
Although both companies operate in competitive environment can in the event of a market imperfection to constitute to the oligarchs even if they practice the commercial policy of discriminatory prices.The naval Steel Construction Company and the People’s Commissary market and distribute fresh food in Kisangani unlike other pairs of companies (Vodacom vs Orange in the communication services, Beltexco vs Plaza in the manufactures’) set the same price for fresh for the same goods and evolve in financial and economic performance.Thus faced with this reality, can we affirm that the groups formed from the tariff schedules of prices of fresh food from these two companies have similar revenue averages to explain the financial performance?Thus, it cannot be said that the average tariff scales of fresh food marketing and distribution companies in Kisangani (RDC) do not differ significantly from financial or profitability.